Formation pressure - temperature (P-T) of Ye Yen Sun granite - Y, Nguyen Viet; Dung, Pham Thi; Hoa, Tran Trong; Anh, Tran Tuan; Hieu, Pham Trung (Vietnam Journal of Earth Sciences, 2019)
Ye Yen Sun Cenozoic granitoid formations include biotite granite, fine- to medium-grained amphibol-biotite granite, and mostly undeformed fine- grained granite porphyry. Temperature calculation by the zircon saturation method gives the formation temperature ranging from about 680°C to 850°C; the pressure, determined on the basis of the major element composition, varies between 10 and 1 kbar (about 33 to 3.3 km deep). The granites viewed as "hot" or "intermediate" magmas were formed at the site of extension or transformation tectonics. Thus, the ability to form these granites due to the melting of the lower crust under the stretching region along the two wings of the Red River shear zone is a mechanism to be considered.